The Market Value of Corporate Votes: Theory and Evidence from Option Prices - KALAY, AVNER; KARAKAŞ, OǦUZHAN; PANT, SHAGUN (Journal of Finance, 2014)
ABSTRACT This paper proposes a new method using option prices to estimate the market value of the shareholder voting rights associated with a stock. The method consists of synthesizing a nonvoting share using put‐call parity, and comparing its price to that of the underlying stock. Empirically, we find this measure of the value of voting rights to be positive and increasing in the time to expiration of synthetic stocks. The measure also increases around special shareholder meetings, periods of hedge fund activism, and M&A events. The method is likely useful in studies of corporate control and also has asset pricing implications.